Elicited Production of Essential Oil with Immunomodulatory Activity in Salvia apiana Microshoot Culture - Agata Krol; Adam Kokotkiewicz; Bozena Zabiegala; Klaudia Ciesielska-Figlon; Ewa Bryl; Jacek Maciej Witkowski; Adam Bucinski; Maria Luczkiewicz (Molecules)
Salvia apiana Jepson is an endemic North American species characterized by a rich phytochemical profile including abietane-type diterpenoids, phenolic acids, flavonoids, and thujone-free essential oil (EO). The current study was aimed at increasing EO production in bioreactor-grown S. apiana microshoot culture through biotic elicitation using chitosan, ergosterol, and yeast extract (YE). Additionally, the immunomodulatory effects of the major volatile constituent of white sage—1,8-cineole—as well as EOs obtained from both S. apiana microshoots and leaves of field-grown plants, were assessed. EOs were isolated via hydrodistillation and analyzed by GC/MS and GC/FID. Biological assays included flow cytometric evaluation of the proliferation and apoptosis rates of human CD4 and CD8 T lymphocytes, obtained from healthy volunteers and subjected to different concentrations of EOs and 1,8-cineole. Elicitation with 100 mg/L YE improved the production of EO in S. apiana microshoots by 9.4% (1.20% v/m). EOs from both microshoots and leaves of field-grown plants, as well as 1,8-cineole, demonstrated dose-dependent anti-proliferative and pro-apoptotic effects on CD4+ and CD8+ T cells. These findings highlight the potential of S. apiana microshoot cultures capable of producing EO with significant immunomodulatory activity.